Byron Redivivus. Issue 1 (1st June 2022) - Allen, Stephen
Abstract : Despite no known recent provenance, an engraved copper printing plate of a Byron portrait has been established to be of considerable significance. Proofs from the plate are held by the National Portrait Gallery and the British Museum. New impressions were made for our purposes. The plate was commissioned by Lieutenant Colonel Leicester Stanhope, who accompanied Byron's body back to England, and was engraved after a miniature painting, which itself has notable associations with Byron.